UV-visible Spectroscopy as a New Tool to Predict the Bioactivity of Humic Fragments Induced by Citric/ Oxalic Acids on Eucalyptus Nutrition and Growth. Issue 22 (15th December 2020) - Morais, Everton; Silva, Carlos Alberto; Maluf, Henrique José Guimarães Moreira
ABSTRACT: Citric (CA) and oxalic (OA) acids are able to change the humic acid (HA) supramolecular structure, affecting HA effects on plants. This study aimed to evaluate the effect of CA and OA on HA supramolecular structure changes, and how these changes influence the eucalyptus growth and nutrition. HA was combined or not with CA and OA, as follows: HA+CA+OA; HA+CA; HA+OA; HA; CA+OA; CA, OA and control (no HA, CA, and OA). Seedlings were grown in a nutrient solution for 45 days. It was determined the dry matter production, the nutrients contained in the nutrient solution, and their accumulation by eucalyptus. Changes in the HA supramolecular structure were evaluated through the UV-visible light absorbance ratios. Use of HA+OA increased the E4/E6 and A254/A204 ratio, and reduced the E2/E3 ratio over the exclusive use of HA, increasing the reactivity and reducing the aromaticity over intact HA. HA fragmented by OA increased the dry matter production and nutrients accumulated by eucalyptus. CA was not effective in changing the HA supramolecular structure, as well as in improving eucalyptus growth. The HA bioactivity on eucalyptus growth induced by CA and/or OA can be inferred from a new index relates to A254/A204 and E4/E6 absorbance ratio.